PENGARUH AKUPRESUR DENGAN TINGKAT NYERI DAN LAMA PERSALINAN KALA I PADA IBU PRIMIPARA DI RSSI PANGKALAN BUN - Isnina, Isnina; Aminatussyadiah, Ayu; Habibah, Aisyah (Jurnal Borneo Cendekia, 2023)
THE EFFECT OF ACUPRESSURE ON PAIN LEVEL AND LONG TIME OF LABOR IN PRIMIPARA MOTHERS IN SULTAN IMANUDDIN HOSPITAL PANGKALAN BUN Acupressure is able to stimulate the release of oxytocin for delivery induction and manage the pain during delivery term. The research is aimed to identify the influence of acupressure toward the delivery pain and its duration of Primiparaous mother. This research used quantitative with cross-sectional design method. Meanwhile, the eighty one- respondent sample of this research were collected from RSSI Pangkalan Bun The result showed that the respondent’s characteristic of mother who treated with and non-acupressure was homogeny (p>alpha, ?: 0, 05) and acupressure influenced toward delivery pain and duration with p<0, 05 significantly. Hence, Acupressure is effectively used in reducing delivery pain level and its duration on the first stage. Key words: Acupressure, delivery duration, delivery pain, non-pharmacological method.